Crossing the threshold of ultrafast laser writing in bulk silicon - Margaux Chanal (Nature Portfolio, 2017)
Ultrafast laser processing is a versatile three-dimensional photonic structuring method but it has been limited to wide band gap materials like glasses. Here, Chanal et al. demonstrate direct refractive-index modification in the bulk of silicon by extreme localization of the energy deposition.